COMMUNICATIVE APPROACH IN TEACHING FOREIGN LANGUAGE - Mamanazarova Rayhona Nurbek qizi, (TADQIQOTLAR, 2025)
Abstract The  communicative  approach,  also  known  as  Communicative  Language Teaching  (CLT),  is one  of the  most  influential  methodologies  in  modern language education. This approach focuses on developing learners’ communicative competence through real-life communication and interactive tasks. The main goal is to help learners use language meaningfully and appropriately rather than merely mastering grammar rules. This paper discusses the theoretical background of CLT, its principles, classroom applications,  and  its  impact  on  modern  foreign  language  teaching.  The  research highlights the balance between fluency and accuracy, emphasizing the learner-centered nature of the communicative approach.